(untitled) (Eurasian Journal of Humanities and Social Sciences, 2023)
In the article, the monetization effect of content intended for children’s audience in YouTube video hosting, the development of critical thinking about media materials in the latest concepts of media education, and practical experience in identifying false information and distortions in the media are presented. Aspects such as the formation of strong immunity against the manipulative influence of transmitted media materials are taken into account.